Strategi Kepala Madrasah Dalam Membangun Prestasi Akademik Peserta Didik Di Mis Mualimin Tabek Nagari Talang Babungo Kabupaten Solok - Gusmaletri; Suswati hendriani; Demina (JURNAL ILMU PENDIDIKAN, 2026)
This study aims to gain an in-depth understanding of the meaning and lived experiences of madrasah principal leadership in enhancing students' academic achievement at Mualimin Tabek Islamic Elementary School (MIS Mualimin Tabek), Talang Babungo Village, Hiliran Gumanti District, Solok Regency, Indonesia. The study employed a qualitative approach using a phenomenological research design, focusing on the subjective experiences of participants regarding the principal's leadership strategies in instructional management and academic development. Data were collected through in-depth interviews, participant observation, and document analysis. The primary informant was the madrasah principal, while teachers and students served as supporting informants. Data were analyzed through the stages of data reduction, data display, and conclusion drawing, while the trustworthiness of the findings was ensured through source and method triangulation. The findings reveal that the principal's leadership strategies are perceived as a collective effort oriented toward strengthening academic development, fostering discipline and a religious school culture, enhancing teachers' professionalism, and providing continuous motivation for students to improve their academic achievement.